Bibliometric analysis of feed additive use in Indonesia: Trends, clusters, and future prospects - Wardi, Wardi; Kusuma, Andri H. A.; Zakariya, Abu Z.; Haq, Miftahush S. (Fakultas Peternakan Universitas Papua, 2025)
Feed additives are essential to improve the efficiency of livestock production and the sustainability of the livestock sector. The study aims to analyze the trend of feed additive research in Indonesia with a bibliometric approach. The method is to collect bibliographic data from Scopus metadata with documents published from 2010-2024. The results of a systematic search collected 51 papers that were analyzed to identify trends and patterns of researchers. The analysis results show that publications regarding feed additives have fluctuated and reached the peak of publications in 2021. The three main clusters identified are (1) the impact of feed additives on livestock productivity, (2) the advancement of bioinformatics in feed formulation, and (3) the investigation of plant secondary metabolites as an alternative to feed additives. In addition, using secondary metabolite compounds from plants as feed additives is predicted to develop in livestock, especially poultry. This bibliometric approach provides strategic insights for future feed additive research, supporting the sustainability of the livestock industry in Indonesia.